Recent advances and future prospects in direct solar desalination systems using membrane distillation technology. (20th January 2023) - Bamasag, Ahmad; Almatrafi, Eydhah; Alqahtani, Talal; Phelan, Patrick; Ullah, Misbah; Mustakeem, Mustakeem; Obaid, M.; Ghaffour, Noreddine
Abstract: Water desalination has become one of the viable solutions for water shortages in regions with limited natural resources. In the last two decades, more attention has been paid to renewable energy resources as an alternative approach in desalination processes. Direct solar desalination technology is considered a sustainable method to provide fresh water for small-scale applications. Several technologies, such as solar stills, solar chimneys, and solar ponds were examined. In the last decade, researchers have proposed direct solar-powered membrane distillation (SP-MD) as an innovative solution to desalinate saline and hypersaline feed water. Membrane distillation (MD) is an emerging thermally-driven desalination technology that operates over a wide range of feed temperatures. Traditionally, the integration of solar energy and MD was indirect (i.e., by having two separate systems: a solar collector and an MD module). Direct SP-MD, however, uses modules that can directly utilize solar energy and desalinate water in a single structure to achieve a more compact, stand-alone design suitable for small-scale applications. In this paper, a comprehensive review of these efforts is discussed. The types of these systems (including surface heating and membrane heating) detailing their advantages and disadvantages are highlighted. The paper also discusses the recent innovations in these units including membrane surface modifications, module structure design, and integration with other systems such as photovoltaic cells. Finally, the paper examines the limitations of these systems and provides future prospects and recommendations.